2015
DOI: 10.4236/ce.2015.617195
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of “Syn-Epistemic Wholeness” from Dialectic Synergy of Disciplines: A Transdisciplinary Social Pedagogic Model

Abstract: Transdisciplinarity offers a different philosophy and approach both of how to effectively address issues/problems and how to improve and change difficult situations we have been experiencing in the modern world, in different and multiple levels of reality and under conditions of complexity and uncertainty. Addressing these problems becomes precisely effective because of the way transdisciplinarity achieves dynamic collaboration and integration among disciplines, epistemologies and methodologies. We could argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
5
0
4
Order By: Relevance
“…The Syneducation Model, among others, interactively connects students' resilience to that of teachers, parents and other adult stakeholders. More specifically, it has been shown that, despite the difference in age, children's resilience through mutual mentoring, is fed and simultaneously feeds that of adults (Mylonakou-Keke, 2015a, 2015b.…”
Section: Discussionmentioning
confidence: 99%
“…The Syneducation Model, among others, interactively connects students' resilience to that of teachers, parents and other adult stakeholders. More specifically, it has been shown that, despite the difference in age, children's resilience through mutual mentoring, is fed and simultaneously feeds that of adults (Mylonakou-Keke, 2015a, 2015b.…”
Section: Discussionmentioning
confidence: 99%
“…Ειδικότερα, ως κοινότητα ορίζεται η τοπική κοινότητα από τη θεσμοθετημένη της μορφή (όπως δήμος, υπηρεσίες που σχετίζονται με τη λειτουργία του σχολείου) μέχρι τη γειτονιά του σχολείου, μέσα στην οποία δραστηριοποιείται η οικογένεια και το σχολείο (Μυλωνάκου-Κεκέ, 2017). Η κοινότητα μπορεί με πολλούς τρόπους -που δεν αφορούν αποκλειστικά την παροχή οικονομικών πόρων-να διευκολύνει τη λειτουργία του σχολείου και να υποστηρίξει δράσεις και πρωτοβουλίες ενισχύοντας και τις σχέσεις σχολείου -οικογένειας -κοινότητας, διαπίστωση η οποία αφορά και τη χώρα μας, σύμφωνα και με τα ερευνητικά αποτελέσματα τελευταίων ετών (Mylonakou -Keke, 2015a, 2015b. Σε αυτόν τον τύπο της εμπλοκής εντάσσονται οι πρακτικές που μπορεί να εφαρμόζουν οι γονείς προκειμένου να αξιοποιήσουν όλους τους διαθέσιμους πόρους στην ευρύτερη κοινότητα για την προαγωγή των δεξιοτήτων γραμματισμού των παιδιών, όπως για παράδειγμα η δανειστική βιβλιοθήκη της γειτονιάς, μια έκθεση βιβλίου, κ.λπ.. Επίσης, ο τύπος αυτός της εμπλοκής αναφέρεται στη συνεργασία σχολείου -οικογένειας -κοινότητας για την από κοινού οργάνωση προγραμμάτων και δράσεων γραμματισμού.…”
Section: η γονική εμπλοκή για τον γραμματισμό υπό το πρίσμα του μοντέ...unclassified
“…Inclusion of socially underprivileged or marginalised pupils emerges in most of the analysed texts as the principal mission or objective of social pedagogues in schools (Ezechil, 2015;Giesecke, 1998;Heimgartner and Sting, 2013;Kornbeck, 2014;Kraav, 2003;Kraus and Hoferkova, 2016;Langager and Vonsild, 2007;Lorenzova, 2018;Madsen, 2013;Mylonakou-Keke, 2015b;Romm, 2016;Storø, 2012;Zemancíková, 2010). Here, social pedagogues could then be a natural element of the school's general support system or pupil health team for pupils with special educational needs.…”
Section: Inclusion Through Interventionsmentioning
confidence: 99%
“…Social pedagogues usually work with individuals in their entire contexts, which may involve cross-boundary efforts in which other milieus are involved, such as pupils' homes, recreational settings and neighbourhoods (Higham, 2001;Paterson et al, 2019;Severinsson, 2010). Tasks may include giving advice, guidance and support to parents, guardians and other key people involved in pupils' lives, but also cooperation with pupil health services, social services and other actors (Bolin, 2010;Heimgartner and Sting, 2013;Kraus and Hoferkova, 2016;Mylonakou-Keke, 2015b). They could also bring attention to the need to change pupils' social conditions or difficult family circumstances .…”
Section: Individual Supportive Interventionsmentioning
confidence: 99%